2011
DOI: 10.1016/j.ijscr.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Giant gallstone: A case report

Abstract: We have been unable to find a report of a larger gallstone in the English or Spanish language medical literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A 12.8 cm x 7 cm gallstone was found within this huge gallbladder, which seems to be the largest gallstone to be removed laparoscopically in the world. While Xu et al detailed the laparoscopic retrieval of a 9.5-cm gallstone, and Becerra et al reported removal of a 16.8-cm long gallstone via classical cholecystectomy in the emergency setting, from the literature to date, our gallstone appears to be the largest removed laparoscopically [6,7].…”
Section: Discussionmentioning
confidence: 84%
“…A 12.8 cm x 7 cm gallstone was found within this huge gallbladder, which seems to be the largest gallstone to be removed laparoscopically in the world. While Xu et al detailed the laparoscopic retrieval of a 9.5-cm gallstone, and Becerra et al reported removal of a 16.8-cm long gallstone via classical cholecystectomy in the emergency setting, from the literature to date, our gallstone appears to be the largest removed laparoscopically [6,7].…”
Section: Discussionmentioning
confidence: 84%
“…The largest reported gall stone hitherto was 17x10cm in size which was reported from Chile. 7 The other two calculi have been reported from Turkey and China measuring 10cm each. 8,9 Gall stones larger than 30mm are associated with an increased risk of developing malignancy.…”
Section: Discussionmentioning
confidence: 96%
“…Singh et al [21] reported a gallstone measuring 12.8 cm x 7 cm and this is mentioned in literature, as the largest gallstone removed through laparoscopic. Otherwise, a giant gallstone measuring 16.8 cm x 7.8 cm x 4.1 cm and weighing 278.0 g was removed by classical open cholecystectomy by Becerra et al [32]. Igwe and Diri [8] in their report of two cases that were successfully managed by lapa roscopic cholecystectomy, recovered a solitary giant gallstone measuring 8.2 cm x 7.5 cm in first case whereas in the second case, there were multiple calculi, one of them being giant with dimensions of 8 cm x 6 cm.…”
Section: Discussionmentioning
confidence: 99%